PERFORMANCE EVALUATION AND ENERGY EFFICIENCY IMPROVEMENT OF AIR CONDITIONING SYSTEM AT HOTEL IN BANDUNG - KHOIRUN NISA (NIM : 13311023); BALQIS AFIFAH (NIM : 13311061); Pembimbing : Ir. FX Nugroho Soe, IKA
The air conditioning system contributes more than 50% of total energy consumption in buildings [1]. Evaluation of the performance of the air conditioning system will significantly influence the energy performance of buildings. The air conditioning system works according to the thermal loads that must be addressed, then the cooling load is need to be calculated to ensure which the air conditioning system has been working in accordance with the thermal load of the building. After the operation of the system is known, the performance of the system can be evaluated then can be obtained how to improve the system performance. In this study, evaluation of the air conditioning system in hotel is done and the ways to to improve the performance of the air conditioning system is searched in order to operate efficiently. By using The CLTD method, the thermal load peak value is obtained by 140 TR. From these assessments showed that the chiller was designed oversized by 22% to handle the thermal load of hotel. Heat transfer rate measurement is used to determine the real cooling loads on the building. The average of heat transfer rate of the chiller-1 and chiller-2 are 37.74 TR and 39.44 TR, where those values is only about 21% of the capacity of the chiller. From the evaluation of the electrical consumption can be obtained that the chiller performance is 2.4 kW/TR, which is decline from the common rating for air-cooled chiller that is 1.29 kW/TR. Energy saving efforts are done based on the real energy consumption and the simulation result of the real conditions by using EnergyPlus software. The payback period by replacing the chiller with the capacity of 50 TR is 23 months and based on electrical energy consumption savings by HVAC system is 9 months. Simulation models of the real conditions using EnergyPlus software generate electrical energy consumption of the real conditions in one year amounted to 3.445.822 kWh. The most electrical consumption is achieved by the air conditioning system that is 59% of the total electrical energy consumption. Design modifications by rising the zone temperature 1Co reduce the total electrical energy consumption 3.82%. Design modifications by rising the zone temperature 2Co reduce electrical energy 6.87%. Design modifications by rising the zone temperature 3Co reduce the electrical energy 9.28%.